1984
DOI: 10.1113/jphysiol.1984.sp015300
|View full text |Cite
|
Sign up to set email alerts
|

Discharges of Purkinje cells in the paravermal part of the cerebellar anterior lobe during locomotion in the cat.

Abstract: SUMMARY1. Extracellular recordings were made from 124 Purkinje cells in the paravermal part of lobule V of the cerebellum in cats walking steadily at a speed of 0-5 m/s on a moving belt.2. All cells tested had a tactile receptive field from which simple spikes could be evoked and 96 % of these were on the ipsilateral forelimb.3. Seventy-six of the cells were also studied whilst the animals sat or lay quietly without movement. Complex spikes were discharged at 1-2/s and these were accompanied by simple spikes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 28 publications
10
84
1
Order By: Relevance
“…Across all 72 Purkinje cells, mean baseline simple spike firing rate calculated from a recording period before CS onset was 26.3 spikes/sec (range = 10.0 to 109.6 spikes/sec). This broad range of tonic activity of simple spikes in Purkinje cells recorded in vivo agrees with many previous studies (Thach 1968;Armstrong and Rawson 1979;Armstrong and Edgley 1984;Edgley and Lidierth 1987). Purkinje cells in the areas we recorded from appeared responsive to the corneal air puff, as bursts of complex spikes could be observed during US-alone trials (Fig.…”
Section: Cerebellar Anterior Lobe Activitysupporting
confidence: 78%
See 1 more Smart Citation
“…Across all 72 Purkinje cells, mean baseline simple spike firing rate calculated from a recording period before CS onset was 26.3 spikes/sec (range = 10.0 to 109.6 spikes/sec). This broad range of tonic activity of simple spikes in Purkinje cells recorded in vivo agrees with many previous studies (Thach 1968;Armstrong and Rawson 1979;Armstrong and Edgley 1984;Edgley and Lidierth 1987). Purkinje cells in the areas we recorded from appeared responsive to the corneal air puff, as bursts of complex spikes could be observed during US-alone trials (Fig.…”
Section: Cerebellar Anterior Lobe Activitysupporting
confidence: 78%
“…Given that the mossy fiber-granule cell-parallel fiber pathway conveys both auditory (Aitkin and Boyd 1975) and tactile (Armstrong and Edgley 1984) information to the cortex, which is represented in Purkinje cells by simple spiking, it might be suggested that the changes in simple spiking after eyeblink conditioning that we observed were more stimulus-than response-related (i.e., CS-and US-related, but not CRrelated). However, the fact that, at least in some Purkinje cells, changes in simple spiking appeared to be related to the CS-US interval suggests that the activity we observed was more than just stimulus-related and may have represented a temporal code.…”
Section: Ditioning (Mccormick and Thompson 1984; Berthier And Moorementioning
confidence: 57%
“…These receptive fields bear a striking similarity to those of the Purkinje cells in this region of cortex (Armstrong & Edgley, 1984b;S. A. Edgley & M. Lidierth, in preparation).…”
Section: Peripheral Receptive Fields Of Golgi Cellsmentioning
confidence: 66%
“…Firstly, and most importantly, none of them ever discharged potentials resembling complex spikes. Secondly, their action potentials were of long duration, ranging from 0-8 to 2-0 ms (as compared to 0-3-1P0 ms for Purkinje cells, see Armstrong & Edgley, 1984b). The action potentials from three different units are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The climbing fiber-driven complex spike activity (Thach, 1967;Armstrong and Edgley, 1984) of a single Purkinje cell recorded at the same location is also illustrated ( Fig. 2 B, raw traces; C, raster and peristimulus time histogram).…”
Section: Resultsmentioning
confidence: 99%